Situating 'best practice': Making healthcare familiar and good enough in the face of unknowns - Harrison, Mia; Rhodes, Tim; Lancaster, Kari (SSM. Qualitative research in health, 2023)
The relationship between ‘best practice’ as a set of evidence-informed principles and its actualization in situations of care has been the subject of significant critique across clinical and sociological health research. Precisely how ‘best practice’ gets done—in practice—is often not investigated in itself. Drawing from qualitative interviews with thirty-three healthcare workers involved in the care, management, and research of Covid-19 in a hospital in Sydney, Australia, we investigate how best practice is done in times of uncertainty and disruption, thus approaching ‘best practice’ as a situated concern. We find that care during Covid-19 is made to work as ‘familiar’ practice, ‘good-enough’ practice, and ‘better’ practice. Our analysis moves away from ideas of best practice as an act, prescription, or framework, towards best practice as processual and always in-the-making. Doing best practice is a situated yet iterative process of making care work in relation with what can be known, what can be done, and what can be done better (here, now, and for now). •Best practice healthcare must be practically made to work in its situation.•Best practice in Covid-19 has often been uncertain, impracticable, and in flux.•Covid-19 care is made familiar, good-enough, and better through situated practices.